2011
DOI: 10.5847/wjem.j.1920-8642.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of high mobility group protein B1 in the lungs of rats with sepsis

Abstract: BACKGROUND:Vibrio vulnifi cus inside the body could activate the NF-κB signaling pathway and initiate the inflammatory cascade. The lung is one of the earliest organs affected by sepsis associated with acute lung injury. High mobility group protein B1 (HMGB1) is an important late-acting pro-infl ammatory cytokine involving in the pathophysiology of sepsis. It is also involved in the injury process in the lung, liver and intestine. There has been no report on the involvement of HMGB1 in Vibrio vulnifi cus sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These results indicated that inflammation would induce the activation of the coagulation system as well as down regulation of physiological anticoagulant mechanisms and inhibition of the fibrinolytic system with the development of sepsis. [11] In addition, our data showed that D-dimer, AT-III, PT and APTT were all signifi cantly related with TNF-α and hs-CRP in patients with critical illness. Plessier et al [12] reported the severity of coagulation dysfunction was closely related to the severity of sepsis in patients with infection.…”
Section: Discussionmentioning
confidence: 57%
“…These results indicated that inflammation would induce the activation of the coagulation system as well as down regulation of physiological anticoagulant mechanisms and inhibition of the fibrinolytic system with the development of sepsis. [11] In addition, our data showed that D-dimer, AT-III, PT and APTT were all signifi cantly related with TNF-α and hs-CRP in patients with critical illness. Plessier et al [12] reported the severity of coagulation dysfunction was closely related to the severity of sepsis in patients with infection.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have shown that LPS positively regulates inflammation by triggering the phosphorylation of p65 and IκB to stimulate the NF-κB pathway and promote the release of inflammatory cytokines (Dong & Yuan, 2018;Duan et al, 2012;Fu et al, 2013;Yang et al, 2020). Further, a relationship between Hmgb1expression and ALI was observed in rats suffering from V. vulnificusor LPS-induced sepsis, with significant pathological injuries in the lungs (Lan et al, 2017;Qiu et al, 2011).…”
Section: F I G U R Ementioning
confidence: 99%
“…[ 15 ] In the present study, the plasma level of uPA in the SIRS group was decreased more significantly than in the non-SIRS group and controls ( P <0.001 and P <0.001; Table 2 , Figure 1 ). Qiu et al[ 22 ] identified that in a clinical situation, frequently characterized by fibrin occlusion of the microcirculation, the ability of polymorphonuclear leukocytes (PMN) to express uPA activity is diminished or absent. Yu et al[ 23 ] demonstrated that dramatically increased plasminogen activator inhibitor type 1 (PAI-1) levels during staphylococcal infection led to a reduction of metabolically active uPA levels.…”
Section: Discussionmentioning
confidence: 99%